2008
DOI: 10.1134/s0033173208070102
|View full text |Cite
|
Sign up to set email alerts
|

Composite polymer-containing protective layers on titanium

Abstract: The method of plasma electrolytic oxidation (PEO) allows for significantly enlarging the sphere of practical application of metals and alloys by modifying their surface properties. PEO coatings, characterized by their good adhesion to substrate and by their developed surfaces, may be an appropriate base for obtaining of composite layers containing polymer materials. In this connection, the application of polytetrafluoroethylene (PTFE) is of considerable interest due to the practical importance of the propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 3 publications
0
12
0
2
Order By: Relevance
“…EðC 5 F 12 Þ; DE ¼ 78 kcal=mol (8) (c -intra-chain radical, t -terminal radical) demonstrated that addition of the CF 3 -group to a radical formed, for example, as a result of irradiation yielded the system stabilization. Here the system stabilization occurs independently of whether the trifluoromethyl group is added inside the chain or at the terminal position.…”
Section: Formation Of Radicals In Fluorocarbon Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…EðC 5 F 12 Þ; DE ¼ 78 kcal=mol (8) (c -intra-chain radical, t -terminal radical) demonstrated that addition of the CF 3 -group to a radical formed, for example, as a result of irradiation yielded the system stabilization. Here the system stabilization occurs independently of whether the trifluoromethyl group is added inside the chain or at the terminal position.…”
Section: Formation Of Radicals In Fluorocarbon Moleculesmentioning
confidence: 99%
“…For example, the basic fluoropolymer -polytetrafluoroethylene (PTFE) -belongs to the class of high-molecular systems of a molecular weight up to one million, whereas accurate calculations are possible only for fragments whose size is limited by a few dozens of atoms. Nevertheless, a number of parameters characterizing the molecular structure of small macromolecules would be also valid for polymers built from the above fragments and, moreover, lowmolecular forms (telomers, fluoro paraffins) themselves have been recently in high practical demand as coatings, nanofilms and composites [7,8]. In the latter case the problem of unambiguous and reliable interpretation of empirical data can be solved by performing quantum chemistry calculations of geometric parameters, conformation, IR-, Raman and NMR-spectra of small macromolecules comprising the polymer forming units [6,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Systematic studies of this powder by the set of physical methods revealed that it contains fractions of different molecular weights, has more complex (in comparison with PTFE) molecular, phase and morphological structure, and radically different thermal parameters . The revealed possibilities for the separation of powder into fractions enabled to isolate low‐, middle‐, and high‐molecular fractions, each of which have its specific features and, as a result, different fields of practical application . The obtained results served as a basis for finer material separation into fractions and their subsequent study.…”
Section: Introductionmentioning
confidence: 98%
“…В связи с этим ПЭОслой позволяет внедрить полимерный материал для модификации покрытия с целью улучшить его защитные характеристики. Наиболее перспективен для этой роли ультрадисперсный политетрафторэтилен, обладающий высокой стойкостью, низкой поверхностной энергией и широким диапазоном температур [8][9][10][11].…”
Section: Introductionunclassified
“…Однако в основном исследуются покрытия, не прошедшие какого-либо срока службы или хранения и находящиеся полностью в условиях лабораторного эксперимента. Указанные в работах [8][9][10][11] показатели защитных свойств покрытий находятся на своих пиковых значениях. Это не дает возможности в полной мере проследить процессы коррозии и разрушения в течение длительного срока эксплуатации или в условиях интенсивного воздействия на них агрессивной среды, чтобы оценить устойчивость сформированных слоев.…”
Section: Introductionunclassified